Synthesis and Biological Activities of Nickel(II), Copper(II) and Zinc(II) Complexes of S-Alkyl dithiocarbazate - Shrivastava, Snehika; Kumar, Anil; Pandey, Yogesh; Dikshit, S.N. (Asian Journal of Chemistry, 2010)
Complexes of S-alkyl dithiocarbazate with transition metal ions, viz., Ni(II), Cu(II) and Zn(II) have been prepared and characterized by infrared, 1H NMR, UV-Vis, elemental analysis and conductivity measurement. All of the synthesized compounds are biologically active and screened for their antibacterial and antifungal activities which are found to exhibit moderate to significant biological activities.